1996
DOI: 10.1007/3-540-61292-0_22
|View full text |Cite
|
Sign up to set email alerts
|

When parents need not have children — Cognitive biases in information modeling

Abstract: Cognitive biases associated with human judgment and choice are widely studied, recognized, and documented in behavioral decision research. It is also well accepted that an understanding and acknowledgment of these biases are vital to mitigate their effects. However, research into cognitive biases in information modeling is virtually lacking. Lest one assumes that research on cognitive biases is irrelevant to the field, information modeling is a cognitively intensive activity and is, thus, highly susceptible to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Some of the more interesting results from Tables 1 and 2 (vi) In terms of the complication in selecting the right connection between object types (i.e., metric 9), class diagrams have the highest count -double that of use case, component and deployment diagrams, and over10 times more complicated than sequence and collaborations diagrams. This is in line with some studies that found users having difficulty in selecting a relationship type between objects/entities (e.g., Siau et al 1995Siau et al , 1996Siau et al , 1997. (vii)As for the complexity of a technique, table 2 shows that class diagrams are the most complex to use followed by component and statechart diagrams (i.e., metric 12).…”
Section: Method-level Metricssupporting
confidence: 83%
“…Some of the more interesting results from Tables 1 and 2 (vi) In terms of the complication in selecting the right connection between object types (i.e., metric 9), class diagrams have the highest count -double that of use case, component and deployment diagrams, and over10 times more complicated than sequence and collaborations diagrams. This is in line with some studies that found users having difficulty in selecting a relationship type between objects/entities (e.g., Siau et al 1995Siau et al , 1996Siau et al , 1997. (vii)As for the complexity of a technique, table 2 shows that class diagrams are the most complex to use followed by component and statechart diagrams (i.e., metric 12).…”
Section: Method-level Metricssupporting
confidence: 83%
“…Numerous laboratory experiments on comparing modelling methods have been conducted (e.g. Jarvenpaa & Machesky, 1989; Jih et al ., 1989; Batra et al ., 1990; Davis, 1990; Batra & Davis, 1992; Siau et al ., 1995; 1996; 1997; Marakas & Elam, 1998; Agarwal et al ., 2000; Kim et al ., 2000; Bodart et al ., 2001; Zendler et al ., 2001). In a laboratory experiment, the researcher assigns subjects to treatment and control conditions, manipulates the independent variables (e.g.…”
Section: Modelling Methods Comparison and Evaluationmentioning
confidence: 99%
“…Every modelling method uses a small set of constructs (Siau et al ., 1996; 1997), which defines the vocabulary of the method. Constructs are concepts, ideas or images specifically conceived for a given modelling method for the purpose of organizing and representing knowledge of interest.…”
Section: Information Modelling Terminologymentioning
confidence: 99%
“…As with the Gemino and Wand framework, CWA does not specify how the cognitive aspects interact with the various modeling techniques, but it does offer us another useful decomposition-decision activities, mental strategies, and cognitive resources. Siau, Wand, & Benbasat (1996) introduce an evaluation approach based on the Theory of Equivalence of Representations (TER) (Simon, 1978). This theory posits that different representations of information may be compared by examining their equivalence to each other in terms of the information they contain and the computational effort required to extract that information.…”
Section: Earlier Work Utilizing Cognitive Theories To Evaluate Modelsmentioning
confidence: 99%